ACCOUNTING INSTRUCTION IN THE LIBERAL ARTS CURRICULUM. - Howard, Stanley E. (The Accounting Review, 1930)
The separation of liberal from non-liberal studies may be attempted on the basis of the content of the several subjects offered. In most conservative quarters "liberal arts curriculum" means a course of study in which emphasis is laid upon linguistics and literature, especially upon the classics of Greece and Rome. Mathematics is by tradition admitted to the liberal arts fold, perhaps because of its disciplinary value, perhaps because by the mastery of its principles one acquires a tool for use in the pursuit of the natural sciences. There appear to be at least three specific objectives of accounting instructions as offered by a liberal arts department of economics. First, it provides students the mastery of a tool which is most useful in the pursuit of other economic studies. In this respect accounting is not unlike a course or courses in statistical method. Secondly problems of taxation, public regulation, and public administration, for example, require for their solution informed intelligence of accounting as well good intentions. Third, accounting study and instruction is not without its disciplinary phases. Many of the most fundamental concepts of accounting are abstractions, as for example, proprietorship, net worth, equities, revenue, expense, profit, loss, gain, income, surplus and reserves.